Satisfaction with Life in Old Age – the Role of Developmental Tasks Attainment and Resiliency - Zadworna-Cieślak, Magdalena; Ogińska-Bulik, Nina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2019)
The late adulthood period is full of challenges which endanger the well-being of an individual and require adaptation. Personal factors such as resiliency and the attainment of developmental tasks typical for the age period play therefore key roles in achieving life satisfaction in old age. The aim of the present study was to determine the roles of resiliency and developmental task attainment in achieving satisfaction with life in old age. One hundred participants of Senior Clubs in their late adulthood, 49 men and 51 women (age range 60-88 years; M = 70.57, SD = 6.71) were surveyed using the Satisfaction with Life Scale (SWLS), Resiliency Measurement Scale (SPP-25) and Developmental Tasks Questionnaire for Seniors (KZR-S). The relationships between variables were determined by correlation, regression analysis and structural equation modeling. The analyses revealed significant relationships between variables. Greater overall resiliency and higher levels of developmental task attainment were associated with greater satisfaction with life, as declared by the respondents. The most significant ones seem to be determination and persistence in action (resiliency factor) and acceptance of one’s life: components of developmental task attainment. Both resiliency and developmental task attainment have a positive impact on the life satisfaction of older people. Greater importance should be attributed to resiliency.